2013
DOI: 10.1108/gs-04-2013-0007
|View full text |Cite
|
Sign up to set email alerts
|

Green supplier selection based on IFS and GRA

Abstract: Purpose -Green supply chain management (GSCM) has become an important issue with increasing awareness of environmental protection. A firm's environmental approach is not only relevant to its inner efforts, but its suppliers' environmental performance is also important. The aim of this study is to propose an integrated multi-criteria decision-making (MCDM) approach based on intuitionistic fuzzy set (IFS) and grey relational analysis (GRA) for green supplier selection. Design/methodology/approach -Green supplier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 61 publications
0
37
0
Order By: Relevance
“…The Green image (GI) criterion deals with establishing the supplier company's business image in the market place as a green supplier with the capability of manufacturing green products which provides a distinctive advantage in the market (Awasthi et al, 2010;Bali et al, 2013;Mafakheri et al, 2011;Tuzkaya, 2013). Green image includes market share, stakeholders' relationships, customer retention, market reputation and staff environmental training (Ghadimi et al, 2015).…”
Section: Green Image (Environmental)mentioning
confidence: 99%
See 1 more Smart Citation
“…The Green image (GI) criterion deals with establishing the supplier company's business image in the market place as a green supplier with the capability of manufacturing green products which provides a distinctive advantage in the market (Awasthi et al, 2010;Bali et al, 2013;Mafakheri et al, 2011;Tuzkaya, 2013). Green image includes market share, stakeholders' relationships, customer retention, market reputation and staff environmental training (Ghadimi et al, 2015).…”
Section: Green Image (Environmental)mentioning
confidence: 99%
“…Fuzzy-casebased reasoning (CBR) Green Bali et al (2013) Develop an approach to cope with situations with partially known and unknown information.…”
Section: Greenmentioning
confidence: 99%
“…When various papers on decision analysis were compared, it is found that several papers cross-referenced fuzzy set theory and rough set theory with artificial intelligence techniques [3,23]. Additionally, various papers discuss fuzzy set theory as an individual methodology in decision making [85][86][87], while the vast majority of papers integrates fuzzy approaches into multi-criteria decision making (MCDM) [88][89][90][91][92][93][94]. This paper examines fuzzy sets as one of the decision analysis tools, and divided these approaches into the sub-techniques depicted in Figure 14.…”
Section: Quantitative Modelsmentioning
confidence: 99%
“…Olugu and Wong [96] defined fuzzy set theory as a knowledge and concept utilization process based on human reasoning. The literature presented a variety of fuzzy focused papers that introduced fuzzy logic as defining membership functions, incomplete preference relationships and linguistic preferences, applying fuzzy arithmetic, fuzzy entropy and fuzzy c-means clustering, utilizing intuitionistic fuzzy sets, fuzzy logic controllers, defining interpretive ranking processes, fuzzy inference systems, fuzzy rule-based systems, and fuzzy axiomatic design (Table A2) [94,[97][98][99][100].…”
Section: Fuzzy Set Theorymentioning
confidence: 99%
“…Rezaei and Ortt (2012) developed a new approach to supplier segmentation, which considers the various variables used in existing literature to segment suppliers. Bali et al (2013) used intuitionistic fuzzy set (IFS) and grey relational analysis (GRA) for green supplier selection. There were eight criteria: service quality, green image, use of green materials, pollution/waste control in production, green product, distribution, reverse logistics and green design or R&D. Deng et al (2014) proposed a methodology for integrated product line design and supplier selection.…”
Section: Literaturesmentioning
confidence: 99%